Correlation of Abnormal Pap Smear with Histologic Outcome In Maharat Nakhon Ratchasima Hospital - Samuttharapaoraya, Jiraporn (Maharat Nakhon Ratchasima Hospital Journal, 2024)
Objective: To determine the correlation of abnormal Pap smear with cervical pathological results in Maharat Nakhon Ratchasima Hospital. Patients and Methods: The retrospective descriptive study was performed by collecting data from cytological and surgical pathology units, department of anatomical pathology, Maharat Nakhon Ratchasima Hospital, Nakhon Ratchasima Province. The specimens (Conventional Pap smear) were collected from the women who attended for cervical cancer screening program during January, 1st -December 31st, 2012. Women with abnormal Pap smear would be further investigated by gynecologists with colposcopic examination. The tissue studied were performed for the abnormalities confirmation using colposcopic directed biopsy (CDB), Endocervical curettage (ECC), Endometrial curettage (EMC), Loop electrosurgical Excision procedure (LEEP) and total hysterectomy. The cytological results and pathological confirmations were compared and analyzed. Results: A total of 6,987 cases of cervical cancer screening were conducted. The abnormal Pap smear found 192 cases and 152 women were confirmed by tissue studies. It was found that women with LSIL cytology were pathologically diagnosed as LSIL 50%, HSIL 20.8% and invasive cancer 8.3%. Women with HSIL cytology were pathological confirmed as HSIL 52.9% and Invasive cancer 29.4%. However, the pap tests interpreted as invasive cancer were pathologically diagnosed as HSIL 16.7% and 83.3% of invasive cancer. Conclusions: Women showed LSIL and HSIL on Pap smear were correlated with cervical pathology as LSIL and HSIL 50%, however in case of invasive cancer, 83.3% were correlated. Women with abnormal Pap smear LSIL and HSIL should be further studied for confirmation. The correlation of cervical cancer was highly found from our study.